Electricity Infrastructure Climate Change Impact Resilience Techniques – A Case Study of the South African Metropolitan Municipalities - Matshonyonge, Busisiwe Charlotte (University of the Witwatersrand, Johannesburg, 2025)
The South African electricity sector faces several challenges which compromise the reliability and stability of municipal electricity service delivery. Factors such as theft, vandalism, lack of investment, load shedding and extreme weather events emanating from climate change impacts, threaten the resilience of electricity infrastructure. The study undertook an investigation to understand the impact of climate change on electricity infrastructure throughout metropolitan municipalities in South Africa. This is imperative to progress the efforts to develop electricity infrastructure resilience techniques. The South African electricity infrastructure is vulnerable to damage and failure due to climate change impacts and human factors such as lack of appropriate maintenance practices, inadequate asset planning, and poor management. These factors threaten the longevity and reliability of electricity service delivery across metropolitan municipalities. A qualitative approach was employed to collect data concerning the current state of electricity infrastructure, and the impact of climate change events and human factors thereupon. The data sample was selected from the metropolitan municipalities in South Africa. Semi-structured, virtually recorded interviews were carried out, with the support of an interview guide which was prepared prior to the interviews. The study findings present the most common challenges faced by metropolitan municipalities as far as the operation and maintenance of electricity distribution infrastructure is concerned. The recurrence of several climate-related incidents and manmade challenges are outlined, and possible solutions to build resilience are proposed. This study found that metropolitan municipalities are aware of the compounding effect of climate change and anthropogenic issues such as infrastructure sabotage and neglect. The key finding showed that the endeavour to enhance the electricity transmission and distribution infrastructure must follow a holistic approach that considers interlinkages between technical performance, financial constraints, human behaviour, and the unpredictability of climate change events. iii As such, holistic suitable electricity infrastructure resilience techniques are proposed as they are fundamental to managing and improving electricity infrastructure resilience. The proposed suitable electricity infrastructure climate change resilience techniques include: improving the management of existing electricity infrastructure, the prioritisation and allocation of dedicated electricity infrastructure maintenance budgets, accelerated implementation of metropolitan municipalities’ existing climate change response strategies, investment into climate impact early warning systems at the municipal level, and an innovative and proactive approach to the development of new electricity transmission and distribution infrastructure. Furthermore, the report concludes with recommendations and suggestions for further research that would enhance metropolitan municipalities' electricity infrastructure resilience against climate change impact.
A research report submitted in fulfillment of the requirements for the Master of Management in Energy Leadership, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Climate Change; Infrastructure, Maintenance; Metropolitan Municipality; SDG-13: Climate action; SDG-7: Affordable and clean energy